Pandangan Hidup Orang Sunda: Refleksi dalam Syair Lagu Mang Koko - Saiful, Abizar Algifari (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2025)
This research aims to examine the reflection of Sundanese worldview in Mang Koko's song lyrics and the process of packaging them into musical works. The method used is qualitative with a phenomenological approach. Data were collected through literature study, documentation, and interviews, then analyzed using content analysis techniques. The results showed that four elements of Sundanese worldview - spiritual, social, moral, and life balance values - were implied in Mang Koko's lyrics that were born from a process of deep contemplation. Song lyrics do not only convey values, but are consciously arranged based on the cognitive and psychological development levels of listeners, ranging from children to the elderly. This shows the principle of humanity that Mang Koko holds dear. He instills normative values of Sundanese character early on through songs, making music an effective educational and cultural medium.